Study on the mechanisms and functions of lncRNAs in regulating carboplatin resistance in ovarian cancer cells - HONG Yi; CHEN Cuilan; YIN Fuqiang; LIU Xia (Guangxi Yike Daxue xuebao)
Objective To screen for differentially expressed long non-coding RNAs (lncRNAs) in carboplatinresistant ovarian cancer (OC) based on expression profiling microarrays and conduct functional enrichment analysis to comprehensively understand the signaling pathways of lncRNAs in response to carboplatin resistance in OC. Additionally, to screen for key lncRNAs regulating carboplatin resistance and explore their molecular mechanisms through functional studies. Methods Differential expressed lncRNAs were screened using expression profiling microarrays in two pairs of carboplatin-resistant and sensitive OC cells (HeyA8-CBP/HeyA8 and SKOV3-CBP/SKOV3). Functional annotation and pathway enrichment of differentially expressed lncRNAs were performed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect lncRNA expression, and western blotting was employed to assess protein expression. Lentiviral transfection was utilized to construct lncRNA DAPK1-IT1 over-expressing cells, colony formation assays were conducted to examine cell proliferation, and flow cytometry was used to analyze cell cycle changes. Results Through expression profiling microarray analysis, 161 stably differentially expressed lncRNAs were identified in two resistant cell lines, including 107 upregulated and 54 down-regulated lncRNAs. KEGG pathway enrichment revealed that the differentially expressed lncRNAs were significantly enriched in classical drug resistance pathways such as the p53 signaling pathway, lysosome, focal adhesion, and immune-related signaling pathways like PPAR. Based on expression profiling microarrays and RT-qPCR validation, lncRNA DAPK1-IT1, which was significantly down-regulated by more than 4-fold in both two carboplatin-resistant cell lines, was selected for functional verification. The results showed that under carboplatin treatment, the colony-forming ability of the carboplatin-resistant OC cells SKOV3-CBP overexpressing lncRNA DAPK1-IT1 was significantly reduced and caused cell cycle arrest at the G2/M phase. Results of western blotting indicated that lncRNA DAPK1-IT1 significantly affected the expression of cell cycle and autophagy-related proteins. Conclusion The expression of lncRNA DAPK1-IT1 is stably down-regulated in carboplatin-resistant OC cells. Its expression inhibits colony formation, arrests cell cycle, and affects cell autophagy. It is a potentially key factor in regulating carboplatin resistance in OC. The p53 signaling pathway, lysosome, PPAR signaling pathway and IL-18 may be the potential pathways for lncRNAs' regulation of carboplatin resistance. These research findings provide new insights for a deeper understanding of the regulation of drug resistance in OC.